Answer:
a)
![\displaystyle{(dG)/(dV_(\text out))=(20)/(V_(\text out)\ln 10)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/paquhkfrtbv5mysa0aqn6ui42c16kznodv.png)
b)
![\displaystyle{\frac{d^2G}{dV_\text{out}^2} = -\frac{20}{V_\text{out}^2\ln 10}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/e5s33s2x5d6w0nbw4hign91584s7ufrr3p.png)
Explanation:
From the given equations to find, we are differentiating function G with respect to V out. Therefore, we will be only using the equation (6):
![\displaystyle{G=20\log (10V_(\text out))}](https://img.qammunity.org/2023/formulas/mathematics/high-school/r4ugucu68br99xrc60mvtpc2wbs94bujv1.png)
Here’s a fresh-up reminders for logarithmic differentiation formula:
![\displaystyle{f(V)=a\log_b V \to f'(x)=(a\cdot V')/(V\ln b)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dd7kwp22af1sjung86xtqm3rcqpfq00b1o.png)
Note that V' means to derive or differentiate the V-term
Therefore, in this scenario, our values of term are:
- a = 20
- b = 10 (Since logarithm base is not shown, it’s always assumed to be common logarithm)
- V = 10V out
Therefore, we can apply differentiation formula:
![\displaystyle{(dG)/(dV_(\text out))=(20\cdot (d(10V_(\text out)))/(dV_(\text out)))/(10V_(\text out)\ln 10)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/igflbi2po999cctoez2stljnxbtc1ntzxs.png)
Simplify:
![\displaystyle{(dG)/(dV_(\text out))=(20\cdot 10)/(10V_(\text out)\ln 10)}\\\\\displaystyle{(dG)/(dV_(\text out))=(20)/(V_(\text out)\ln 10)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6nyvfhghllidnluofr2gop8l1z1sjh48ax.png)
And we have finished the part a. On part b, we just differentiate the answer from part a again, the second part is to obtain the second derivative which is to derive the first derivative. Therefore:
![\displaystyle{(d^2G)/(dV_(\text out)^2) = (d\left((20)/(V_(\text out)\ln 10)\right))/(dV_(\text out))}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8v30k40r75jlg9jyxo9m4a05ynnt90brqv.png)
First, separate the constant every time when you have to differentiate a function:
![\displaystyle{(20)/(\ln 10)\cdot (1)/(V_(\text out))}](https://img.qammunity.org/2023/formulas/mathematics/high-school/tjazyb8d3uzxf6z0u67rfieaa76dctfxos.png)
Differentiate 1/V out: recall the formula of fraction:
![\displaystyle{f(V)=(1)/(V) =V^(-1) \to f'(x)=-V^(-2) = -(1)/(V^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/2i9obyg2tuma2qe27tcnpwca0wvwjpvkcf.png)
The formula above is derived from power rules formula where:
![\displaystyle{f(V)=V^n = nV^(n-1)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/mx1xpdu24o0e14snsr2tdbi1u8ohudouoz.png)
Therefore, from the function of V out:
![\displaystyle{\frac{d^2G}{dV_\text{out}^2} = (20)/(\ln 10) \cdot \left(\frac{1}{V_\text{out}}\right)'}\\\\\displaystyle{\frac{d^2G}{dV_\text{out}^2} = (20)/(\ln 10) \cdot (V_\text{out})^(-1)}\\\\\displaystyle{\frac{d^2G}{dV_\text{out}^2} = (20)/(\ln 10) \cdot (-V_\text{out})^(-2)}\\\\\displaystyle{\frac{d^2G}{dV_\text{out}^2} = (20)/(\ln 10) \cdot \left(-\frac{1}{V_\text{out}^2}\right)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nghlleas84x3wtgxgin3gvn6r09rpatifs.png)
Simplify to latest as we get:
![\displaystyle{\frac{d^2G}{dV_\text{out}^2} = -\frac{20}{V_\text{out}^2\ln 10}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/e5s33s2x5d6w0nbw4hign91584s7ufrr3p.png)
Please let me know if you have any questions!